The Method of Moving Planes for Integral Equation in an Extremal Case (Journal of Partial Differential Equations, 2016)
In this paper, we study the symmetry results and monotonicity of solutions for an integral equation $$u(x)=-c_N∫_{\mathbb{R}^N}e^{u(y)}log|x-y|dy$$ in an external case.
Keywords: Integral equation; radial symmetry; the method of moving planes